2007
DOI: 10.1523/jneurosci.0334-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

From Hunger to Satiety: Reconfiguration of a Feeding Network byAplysiaNeuropeptide Y

Abstract: A shift in motivational state often produces behavioral change, but the underlying mechanisms are poorly understood. In the marine mollusc, Aplysia californica, feeding-induced transition from a hunger to satiation state leads to a slowdown and an eventual termination of feeding. Because the multifunctional feeding network generates both ingestion and the competing response, egestion, it is possible that the transition from a hunger to a satiety state is associated with network reconfiguration that results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
109
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 73 publications
3
109
1
3
Order By: Relevance
“…Immunocytochemistry (whole mount) was performed as described previously (Furukawa et al, 2001;Jing et al, 2007). Central ganglia were fixed in 4% paraformaldehyde, 0.2% picric acid, 25% sucrose, and 0.1 M NaH 2 PO 4 , pH7.6, for either 3 h at room temperature or overnight at 4°C.…”
Section: Immunocytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Immunocytochemistry (whole mount) was performed as described previously (Furukawa et al, 2001;Jing et al, 2007). Central ganglia were fixed in 4% paraformaldehyde, 0.2% picric acid, 25% sucrose, and 0.1 M NaH 2 PO 4 , pH7.6, for either 3 h at room temperature or overnight at 4°C.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…The Aplysia feeding circuit generates a rhythmic pattern of repetitive protraction-retraction sequences Jing et al, 2009), with protraction initiated first followed by retraction. Previous work has shown that many critical neurons that play important roles in the generation of protraction are cholinergic.…”
Section: Glutamatergic Actions In Aplysia Feeding Circuitmentioning
confidence: 99%
“…It will be important to distinguish brainstem systems for respiration, cardiovascular control, and swallowing from those involved in nausea and vomiting. Studies in invertebrate systems reveal overlapping neural architecture that simply switches between "behavioral states" (e.g., rejection and ingestion responses in the marine snail Aplysia, Jing et al, 2007) and this also seems operative in mammals (e.g., the role of the respiratory network in the emetic response: Fukuda et al, 2003). The sensory pathways for nausea and vomiting are generally well understood (e.g., vagal and vestibular inputs) but the pivotal problem of defining the convergent neural circuitry that generates nausea and vomiting is still largely unsolved.…”
Section: Neurobiology Of Nausea and Vomitingmentioning
confidence: 99%
“…D ifferent forms of rhythmic neural output are ubiquitously observed in motor behaviors such as locomotion, respiration, and feeding (1)(2)(3)(4). Extensive research has revealed that a neural network can switch among alternate rhythms by altering the properties of specific intrinsic membrane currents and synapses (5).…”
mentioning
confidence: 99%